2010
DOI: 10.1007/s10597-010-9357-6
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Services for Children of Substance Abusing Parents: Voices from the Community

Abstract: This qualitative study explores how to improve services for children of parents with Substance Use Disorders (SUD) with unmet mental health needs. Focus groups were conducted with parents and caregivers to identify perceived barriers to services, including: (1) attitudes and beliefs about mental health care, (2) inadequacies in mental health services, (3) children's ambivalence about treatment, and (4) parental disagreement and lack of involvement. Peer support, afterschool activities, and family counseling we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…12 Our data suggest the need for early intervention in high-risk families with methamphetamineusing parents. As suggested by Contractor et al, 29 family-based programs should include comprehensive substance use treatment for parents, family counseling, peer support, and after-school activities for the children of parents with substance use disorders.…”
Section: Discussionmentioning
confidence: 99%
“…12 Our data suggest the need for early intervention in high-risk families with methamphetamineusing parents. As suggested by Contractor et al, 29 family-based programs should include comprehensive substance use treatment for parents, family counseling, peer support, and after-school activities for the children of parents with substance use disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Negative perceptions of providers and treatment (e.g. mistrust of mental health professionals, concerns about violations in confidentiality; Contractor et al., ; McKay & Bannon, ), the perceived relevance and helpfulness of therapeutic approaches (Eapen & Ghubash, ; Kazdin, Holland, Crowley, & Breton, ; Morrissey‐Kane & Prinz, ; Nock & Kazdin, ) and their acceptability (Choi & Kovshoff, ; Stevens, Kelleher, Ward‐Estes, & Hayes, ), are powerful drivers of service utilization and underuse. Expectancies such as the perceived usefulness of treatment (Graf, Grumm, Hein, & Fingerle, ) and its acceptability (MacKenzie, Fite, & Bates, ) are also associated with child treatment outcomes, including reductions in child problem behaviors, although this literature is considerably thinner than the association between these factors and engagement in care.…”
Section: Introductionmentioning
confidence: 99%
“…For example, numerous factors across different studies have been associated with service utilization, making it a complex task to discern patterns from these data. Previous studies have demonstrated the importance of parental attitudes towards mental health services service engagement, where dissatisfaction and lack of trust in the system (Baker-Ericzén et al 2013;Contractor et al 2012), and negative help-seeking (Logan and King 2001;McKay et al 2001) are shown to be consistent contributors to lower rates of service utilization among families. Further, perceptions of stigma around mental health services may decrease parental help-seeking and, therefore, service utilization (Dempster et al 2013;Gronholm et al 2015).…”
Section: Introductionmentioning
confidence: 98%